The relationship of neutrophil elastase and proteinase 3 with risk factors, and chronic complications in type 2 diabetes: A Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) sub-study. (July 2021) - Ong, Kwok-Leung; Wu, Liang; Januszewski, Andrzej S; O'Connell, Rachel; Xu, Aimin; Scott, Russell S; Sullivan, David R; Rye, Kerry-Anne; Li, Huating; Ma, Ronald CW; Li, Liping; Gebski, Val; et al.
Introduction: Neutrophil elastase (NE) and proteinase 3 (PR3) are novel inflammation biomarkers. We investigated their associations with chronic complications, determinants of biomarker levels and effects of fenofibrate in patients with type 2 diabetes mellitus (T2DM) from Fenofibrate Intervention and Event Lowering in Diabetes study. Methods: Plasma NE and PR3 levels were quantified at baseline ( n = 2000), and relationships with complications over 5-years assessed. Effects of fenofibrate on biomarker levels ( n = 200) were determined at four follow-up visits. Results: Higher waist-to-hip ratio, homocysteine and C-reactive protein and lower apoA-II were determinants of higher NE and PR3 levels. Higher NE levels were associated with on-trial stroke and cardiovascular mortality, and higher PR3 levels with on-trial stroke, but associations were not significant after adjustment for confounding factors. Although higher NE and PR3 levels were associated with baseline total microvascular disease, only NE levels were associated with on-trial neuropathy or amputation. These associations were not significant after adjusting for multiple comparisons. NE and PR3 levels did not change with fenofibrate. Conclusions: In T2DM plasma NE and PR3 levels are associated with vascular risk factors, and total microvascular disease at baseline, but on rigorous analyses were not associated with on-trial complications. Levels were not changed by fenofibrate.